Antiviral immunity within neural stem cells distinguishes Enterovirus-D68 strain differences in forebrain organoids - Christine Vazquez; Seble G. Negatu; Carl D. Bannerman; Sowmya Sriram; Guo-Li Ming; Kellie A. Jurado (Journal of Neuroinflammation)
Abstract Neural stem cells have intact innate immune responses that protect them from virus infection and cell death. Yet, viruses can antagonize such responses to establish neuropathogenesis. Using a forebrain organoid model system at two developmental time points, we identified that neural stem cells, in particular radial glia, are basally primed to respond to virus infection by upregulating several antiviral interferon-stimulated genes. Infection of these organoids with a neuropathogenic Enterovirus-D68 strain, demonstrated the ability of this virus to impede immune activation by blocking interferon responses. Together, our data highlight immune gene signatures present in different types of neural stem cells and differential viral capacity to block neural-specific immune induction.